1998
DOI: 10.1121/1.421218
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modality matching and the loudness growth function for click stimuli

Abstract: Loudness-intensity functions for click stimuli were obtained from 30 adult listeners having normal (n = 10), flat (n = 10), or sloping (n = 10) high-frequency cochlear hearing loss configurations. The procedure of cross-modality matching (CMM) between loudness and perceived line length [R. P. Hellman and C. H. Meiselman, J. Speech Hear. Res. 31, 605-615 (1988); J. Acoust. Soc. Am. 88, 2596-2606 (1990); J. Acoust. Soc. Am. 93, 966-975 (1993)] was used to validate their loudness growth functions. Mean group loud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Both methods yielded consistent slope estimates across frequencies, but the CMM method was more reliable in the sense that the standard deviation for the slope estimates ͑last row͒ was an order of magnitude smaller than that of ME ͑0.09 vs. 0.71 for 1 kHz, and 0.08 vs. 0.72 for 4 kHz͒. This observation is consistent with similar studies that use CMM and ME ͑e.g., Serpanos et al, 1998;Collins and Gescheider, 1989͒. The average estimated slope was within the range of those reported in the literature: Epstein and Florentine ͑2005͒ reported a mid-to-high-level slope of about 0.18 ͑using uncorrected CMM͒, Hellman ͑1991͒ reported a slope of 0.3, Serpanos et al ͑1998͒ reported a value of 0.32, Collins and Gescheider ͑1989͒ reported a value of 0.292, McFadden ͑1975͒ observed individual values between 0.14 and 0.24, and Stevens ͑1966͒ reported a value of 0.32.…”
Section: A Psychoacoustical Resultsmentioning
confidence: 99%
“…Both methods yielded consistent slope estimates across frequencies, but the CMM method was more reliable in the sense that the standard deviation for the slope estimates ͑last row͒ was an order of magnitude smaller than that of ME ͑0.09 vs. 0.71 for 1 kHz, and 0.08 vs. 0.72 for 4 kHz͒. This observation is consistent with similar studies that use CMM and ME ͑e.g., Serpanos et al, 1998;Collins and Gescheider, 1989͒. The average estimated slope was within the range of those reported in the literature: Epstein and Florentine ͑2005͒ reported a mid-to-high-level slope of about 0.18 ͑using uncorrected CMM͒, Hellman ͑1991͒ reported a slope of 0.3, Serpanos et al ͑1998͒ reported a value of 0.32, Collins and Gescheider ͑1989͒ reported a value of 0.292, McFadden ͑1975͒ observed individual values between 0.14 and 0.24, and Stevens ͑1966͒ reported a value of 0.32.…”
Section: A Psychoacoustical Resultsmentioning
confidence: 99%
“…The body lengths of the smiling caterpillars were 0.52, 1. 04, 2.08, 5.2, 10 .4, 20 .8, 41 .6, and 65 cm (a ratio of 125:1), in accord with the line lengths used in recent CMM studies with adults (e .g., Hellman and Meiselman, 1988, 1990, 1993Hellman, 1999 ;Serpanos et al, 1998). The width of each line and size of the affixed graphic (the "face" of the caterpillar) was identical for each line length .…”
Section: Stimulimentioning
confidence: 99%